Daniel's Knee Injuries : Ligament and Cartilage Structure, Function, Injury, and Repair. - Pedowitz, Robert A. (Wolters Kluwer Health, 2003)
As a follow-up of the highly acclaimed work published in 1990, this Second Edition focuses on everything related to the knee ligaments. This edition has more clinical information, and features a new surgical section. Drs. Pedowitz, O'Connor, and Akeson examine the ligament from cell to patient, including biology, biomechanics, and clinical treatment. Since the past decade has shown tremendous expansion in the realm of knee ligament research, this edition was compiled with the strategy to bring everything into one convenient reference. A CD-ROM featuring narrated animations of functional biomec.